Kesadaran Hukum Masyarakat dalam Akselerasi Sertifikasi Tanah Wakaf di Kota Malang - Sudirman, Sudirman; Ramadhita, Ramadhita (Fakultas Syariah, 2020)
This research is motivated by the enthusiasm of the Malang City Government to promote the certification of waqf land whose legal status is uncertain. Data shows that certified wakaf land is only 45.6% while certified wakaf land is still 54.4%. The main purpose of this study is to describe the factors that cause uncertified waqf land in Malang City, to illustrate the real efforts of the Malang City Government to increase public legal awareness, and to analyze the Malang City community's views on endowment land certification. using legal awareness theory. The results showed that the factors behind uncertified waqf land were the low level of legal awareness of the people of Malang City, high costs, and long complicated procedures for obtaining certificates. Therefore, the government has introduced a number of policies to resolve the problem, such as legal education and free registration of waqf land. Finally, the analysis of legal awareness theory shows that the people of Malang City have an intermediate range of legal awareness due to the cognitive level of legal regulation, the content of cognitive level regulation, legal attitude, and legal behavior Penelitian ini dilatarbelakangi oleh antusiasme Pemerintah Kota Malang untuk mempromosikan sertifikasi tanah wakaf yang status hukumnya masih belum pasti. Tujuan artikel ini adalah untuk mendeskripsikan faktor-faktor yang menyebabkan tanah wakaf tidak bersertifikat di Kota Malang, untuk menggambarkan upaya nyata pemerintah Kota Malang untuk meningkatkan kesadaran hukum publik, dan untuk menganalisis pandangan masyarakat Kota Malang tentang sertifikasi tanah wakaf. Hasil penelitian menunjukkan bahwa faktor-faktor di balik tanah wakaf tidak bersertifikat adalah rendahnya tingkat kesadaran hukum masyarakat Kota Malang, biaya tinggi, dan prosedur rumit panjang untuk mendapatkan sertifikat. Oleh karena itu, pemerintah telah memperkenalkan beberapa kebijakan untuk menyelesaikan masalah, seperti pendidikan hukum dan pendaftaran gratis untuk tanah wakaf. Akhirnya, analisis teori kesadaran hukum menunjukkan bahwa masyarakat Kota Malang memiliki rentang kesadaran hukum menengah karena tingkat kognitif regulasi hukum, isi regulasi level kognitif, sikap hukum, dan perilaku hukum.Kata Kunci: waqf tanah; sertifikat; kesadaran hukum